The burden of informal family caregiving in Europe, 2000–2050: a microsimulation modelling studyResearch in context - Andrea Cattaneo; Andrea Vitali; Daniele Regazzoni; Caterina Rizzi (The Lancet Regional Health. Europe)
Summary: Background: The demand for informal care in Europe is increasing, with family members often providing essential support. However, the future burden of informal family caregiving remains unclear. This study estimates and projects trends in the burden of family caregiving across 31 European countries from 2000 to 2050. Methods: We developed a demographic microsimulation model to estimate and project family care burden. The model produces virtual populations with realistic kinship networks and health trajectories over time. From these kinship structures, we defined a novel metric – Years Lived Caregiving for older relatives (YLCs). It accounts for care recipients’ disability severity, care dynamics within kinship networks, and national institutional care capacity. Model inputs included demographic data from UN World Population Prospects, marital statistics from Eurostat, disease prevalence from the Global Burden of Disease study, and microdata from the SHARE survey. Findings: From 2000 to 2050, in Europe the overall burden for informal care is projected to increase by +49.7% (95% UI 45–53.6), from 7.98 (7.65–8.28) to 11.9 (11.4–12.5) million YLC. Musculoskeletal disorders are the largest cause of care burden, contributing to 2.3 (2.18–2.42) million YLC in 2050. Burden of informal care is disproportionally higher for women, although the gender gap is in a descending trend. Interpretation: Projections indicate a substantial rise in the informal family care burden across Europe by 2050, with only limited offsetting from institutional care. These findings underscore the need for comprehensive strategies to support both caregivers and care recipients, ensuring sustainable healthcare systems across Europe. Funding: Italian government and the European Union, National Plan for NRRP Complementary Investments (PNC).